Analysis of Bioactive Components in the Fruit, Roots, and Leaves of Alpinia oxyphylla by UPLC-MS/MS. (10th July 2021) - Ying, Li; Wang, Deli; Du, Guankui
Abstract : Alpinia oxyphylla ( A. oxyphylla ) fruit has long been used in traditional Chinese medicine. In our study, the bioactive components of its roots, fruit, and leaves were investigated, and their potential medical value was predicted. The root, fruit, and leaf samples were analyzed using a UPLC-MS/MS system. The mass spectrometry outcomes were annotated by MULTIAQUANT. The "compound-disease targets" were used to construct a pharmacology network. A total of 293, 277, and 251 components were identified in the roots, fruit, and leaves, respectively. The fruit of A. oxyphylla had a higher abundance of flavonols. The roots of A. oxyphylla were enriched in flavonols and phenolic acids. The leaves of A. oxyphylla exhibited high contents of flavonols, phenolic acids, and tannins. Furthermore, network pharmacology analysis showed that flavonoids are the most important effectors in the fruit of A. oxyphylla and phenolic acids are the most important effectors in the roots and leaves. Moreover, the results suggested that the tissues of A. oxyphylla might play a role in the regulation of disease-related genes. The whole plant of A. oxyphylla is rich in natural drug components, and each tissue has high medicinal value. Therefore, comprehensive utilization of A. oxyphylla can greatly improve its economic value.